CCL4L2 is a potential biomarker for differentiating central and peripheral vertigo - Hong, Xia; Li, Yuan; Tao, Chenjuan; Wang, Gaofeng (Frontiers in Integrative Neuroscience, 2025)
BackgroundCentral vertigo and peripheral vertigo are common clinical conditions with different underlying pathophysiologies. The identification of reliable biomarkers for differential diagnosis remains a challenge.ObjectivesThis study aimed to explore the differential expression of CCL4L2 in the serum of patients with central and peripheral vertigo and assess its diagnostic potential.MethodsA total of 180 patients (90 central vertigo, 90 peripheral vertigo) were enrolled. RNA sequencing was on serum samples to identify differentially expressed genes (DEGs). Kyoto encyclopedia of genes and genomes (KEGG) pathway enrichment analysis revealed relevant biological pathways. The expression of CCL4L2 was measured using RT-qPCR, and its diagnostic performance was evaluated by Receiver operating characteristic (ROC) curve analysis. The correlation between CCL4L2 expression and biomarkers NSE and S100β was also assessed.ResultsRNA sequencing revealed significant differences in gene expression between central vertigo and peripheral vertigo groups. The KEGG pathway analysis identified several enriched pathways, including NF-κB signaling, where CCL4L2 was a key gene. CCL4L2 expression was significantly higher in the CV group compared to the PV group (p < 0.001). ROC analysis demonstrated high diagnostic accuracy for CCL4L2 in distinguishing CV from PV (AUC = 0.909, p < 0.001). Additionally, moderate positive correlations were observed between CCL4L2 and NSE (r = 0.475, p < 0.001), and a weaker correlation with S100β (r = 0.364, p < 0.001).ConclusionCCL4L2 may serve as a potential biomarker for differentiating central from peripheral vertigo. Its expression is closely associated with inflammatory pathways, making it a promising target for further investigation in vertigo diagnostics.